Rancang Bangun Simulator Smart Home Berbasis IoT Dengan Sumber Daya PLTS - Servinus, Servinus; Kumara, I Nyoman Satya; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2024)
Electrical energy is one of the basic needs to support daily life. Renewable energy sources are an alternative that can be used as a source of electrical energy, one example is solar energy. This research aims to be able to create a control and monitoring system for electrical equipment loads based on the Internet of Things, to be able to simulate this tool as a test the system as a whole, starting from the power source to the devices to be controlled. The simulation results in the design show monitoring of load (charger smartphones) and then the system can control it by disconnecting the power source by an automatic relay which is connected to the Esp-Wroom32 via a WiFi network so that the system can run according to the user's needs. Keywords - Smart Home; Energy Consumption Intensity; System Monitoring; Smart Control; Esp-Wroom32.